Problem Solving Ability Relationship and Critical Thingking with Student PAI Learning Outcomes in State Junior High School, Tarumajaya District, Regency. Bekasi - Lestari, Yunia; Khoir, Abdul; Suryantoro (Proceeding International Conference on Education, 2023)
Learning outcomes are one indicator of the success or failure of learning. Several indicators influence learning outcomes, including the ability to solve problems and critical thinking skills. This study aims to determine the relationship between problem-solving and critical thinking skills together with the learning outcomes of PAI students at junior high schools in Tarumajaya District, Kab. Bekasi. The method used is a quantitative method with a correlational approach. Data analysis techniques using the Paired T-Test, Anova Test and Test the coefficient of determination using the SPSS application. The sample was based on the Slovin formula of 283 students from a population of 967 students taken from grade 7 at SMPN. The results of this study indicate that the research hypothesis is proven to have a value of Py12 > 0, which explains that there is a positive relationship between problem-solving abilities (X1) and critical thinking (X2) together with Islamic education learning outcomes of students (Y) in public junior high schools in Tarumajaya District, Kab. Bekasi means that X1 and X2 jointly affect Y. Meanwhile, X1 and X2 also partially affect Y.